Optimalisasi Produksi Biogas dengan Sistem Monitoring Berbasis IoT Pendampingan Masyarakat Berkelanjutan Kelompok Tani Guo Mandiri di Kelurahan Kuranji Kota Padang - Herix Sonata; Firmansyah David; Eko Kurniawanto Putra (CANANG: Jurnal Pengabdian Masyarakat, 2025)
Biogas production as a renewable energy source has great potential in supporting energy security and environmental sustainability. This article discusses the optimization of biogas production through the application of an Internet of Things (IoT)-based monitoring system implemented by the Guo Mandiri Farmer Group in Kuranji Village, Padang. The IoT monitoring system enables real-time monitoring of fermentation conditions such as temperature, pH, and pressure, allowing for more efficient control of the production process. Continuous community assistance is an important factor in increasing technological management capacity and implementation success. The results show that the integration of this technology can significantly increase the volume and quality of biogas as well as strengthen the role of the community in the development of independent energy. This community service provides recommendations for the development of community-scale biogas through technology and participatory approaches for sustainability.